Common and differential dimensions of personal identity between psychosis and depression: The relevance of gender and depressive mood. (August 2020) - García-Mieres, H.; Montesano, A.; Villaplana, A.; Trujillo, A.; Salla, M.; Paz, C.; Ochoa, S.; Feixas, G.
Abstract: Disturbances in personal identity are recognized in psychosis and depression. However, it is unknown whether these disruptions share common processes across clinical groups, or whether there are unique alterations by group or between men and women within each clinical group. To advance on this question, we compared personal identity dimensions in psychosis and depression and investigated the effects of gender and depressive mood. This study assessed dimensions of personal identity using the repertory grid technique among 85 outpatients with psychosis, 85 outpatients with depressive disorders and 85 healthy controls who were matched by age. Data regarding depressive mood and general functioning was also collected. Results showed that self-discrepancies were higher in psychosis and depression than in controls, and were associated with depressive mood. Interpersonal dichotomous thinking was more prevalent in women in both clinical groups. Women with psychosis showed higher ideal-others discrepancy and had a more complex structure of personal identity than their male counterparts. To conclude, alterations in self-ideal and self-others discrepancies may be transdiagnostic dimensions related to depressive mood. Interpersonal dichotomous thinking may also be a common dimensional characteristic in psychosis and depression but more specific to women. Finally, critical views of others and a higher complexity of personal identity may be more specific to women than men with psychosis. Our results are consistent with other studies pointing to the need for person-focused treatments promoting the recovery of a full sense of personal identity, rather than just focusing on specific thoughts and feelings. Highlights: Interventions focusing on self-discrepancies could be applied transdiagnostically to psychosis and depression. Women with psychosis might be the group most affected by feelings of resentment. Women with psychosis or depression may benefit from working therapeutically with the use of more modulated ''shades of grey'' in evaluations of self and others. Men with psychosis have a greater need for the development of the differentiation of representations of self and others and on incorporating more meaningful dimensions.